IMPLEMENTASI ABSENSI FINGERPRINT SISWA TERHADAP KEDISIPLINAN SISWA - Mohammad Farhan Yusup; Eva dwi kumala sari (STIT Al-Marhalah Al-Ulya Bekasi, 2022)
The purpose of this study was to find out disciplined students with the implementation of fingerprint attendance. This study uses a mixed method (a combination of quantitative and qualitative). In this study, data collection was carried out in various ways, such as questionnaires, interviews and documentation. Respondents were asked to fill in several statements related to the application of fingerprint attendance and student discipline. Analysis of the data in this study using simple regression (Simple Linear Regression). The results showed that there was a positive influence between the application of student fingerprint attendance and student discipline as indicated by the value of sig. p-value = 0.000 0.05 then H0 is rejected H1 is accepted. When viewed from the model summary student fingerprint attendance affects student discipline by 26.3% and this is included in the low category. Based on the results of the study, only the majority of students used fingerprint attendance at school. therefore the application of student fingerprint attendance must continue to be improved in order to have a significant role in improving student discipline, especially in their attendance at school. Keywords : Fingerprint, Attendance, Student Discipline.